2014
DOI: 10.1101/gad.240762.114
|View full text |Cite
|
Sign up to set email alerts
|

MZB1 is a GRP94 cochaperone that enables proper immunoglobulin heavy chain biosynthesis upon ER stress

Abstract: MZB1 (pERp1) is a B-cell-specific and endoplasmic reticulum (ER)-localized protein implicated in antibody secretion and integrin-mediated cell adhesion. Here, we examine the role of MZB1 in vivo by conditional gene inactivation in the mouse germline and at different stages of B lymphopoiesis. Deletion of MZB1 impairs humoral immune responses and antibody secretion in plasma cells that naturally undergo ER stress. In addition, we found that experimental induction of ER stress by tunicamycin injections in mice r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
103
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 61 publications
(74 reference statements)
3
103
0
1
Order By: Relevance
“…Scientists from the Max Planck Institute of Immunobiology and Epigenetics (MPI-IE) have now shown that the protein MZB1 has a stress-reducing effect on the cell. 28 The protein apparently helps newly-forming antibodies to adopt their correct structure. Studies indicate that there are dramatic differences in MZB1 gene expressions between the chronic and aggressive periodontitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Scientists from the Max Planck Institute of Immunobiology and Epigenetics (MPI-IE) have now shown that the protein MZB1 has a stress-reducing effect on the cell. 28 The protein apparently helps newly-forming antibodies to adopt their correct structure. Studies indicate that there are dramatic differences in MZB1 gene expressions between the chronic and aggressive periodontitis patients.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the expression of the Ig surrogate light chain genes VpreB and Igll1 (encoding λ5) is down-regulated in EBF1H240A-expressing cells relative to EBF1wt-expressing cells. In addition, we observed a reduced expression of Rag1, Pou2af1 (encoding OcaB), and Mzb1, encoding an ER-resident cochaperone that influences the folding of the Ig µ heavy chain and helps to buffer the effects of DNA damage in early B-lineage cells (Rosenbaum et al 2014). In support of a role of the interaction of the CCR4-NOT complex with EBF1, we observed a similar developmental block in Cnot3 fl/fl RERT Cre mice in which the second and third exons were deleted upon tamoxifen treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, we suggest that the effect of Cnot3 deficiency on Igh recombination is indirect via a reduced autoregulation of Ebf1 and reduced expression of Pax5. Moreover, the altered expression of p53 is not observed in Cnot3 fl/fl RERT Cre mice and may be linked to the genotoxic stress observed in pro-B cells of the mb1 Cre mouse line (Rosenbaum et al 2014). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations